PENGARUH KESEHATAN, KESELAMATAN DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN PT. TJIWI KIMIA MOJOKERTO - Mochammad Fatkhur Rhohman; Nugroho Mardi Wibowo (Jurnal Ekonomi, Bisnis dan Social, 2024)
This study aims to identify the effect of occupational health, occupational safety, and work environment on employee performance at PT Tjiwi Kimia Mojokerto. The research method used is quantitative method with multiple regression analysis. Data were collected from 75 paper production employees using questionnaires and documentation. The results of the analysis show that occupational health, occupational safety, and work environment have a positive effect on employee performance. Employees who have good occupational health and safety and a conducive work environment have better performance. The health variable has a positive and significant influence partially on employee performance at PT Tjiwi Kimia Mojokerto. The safety variable also has a partially positive and significant effect on employee performance at PT. Tjiwi Kimia Mojokerto. The work environment variable also has a partially positive and significant effect on employee performance at PT. Tjiwi Kimia Mojokerto. Health variables, safety variables, and work environment variables together have a significant effect on employee performance at PT. Tjiwi Kimia Mojokerto.